A Dry‐Processed Al2O3/LiAlO2 Coating for Stabilizing the Cathode/Electrolyte Interface in High‐Ni NCM‐Based All‐Solid‐State Batteries. Issue 8 (9th November 2021) - Negi, Rajendra S.; Yusim, Yuriy; Pan, Ruijun; Ahmed, Shamail; Volz, Kerstin; Takata, Ryo; Schmidt, Franz; Henss, Anja; Elm, Matthias T.
Abstract: Due to their high theoretical energy densities and superior safety, thiophosphate‐based all‐solid‐state batteries (ASSBs) are considered as promising power source for electric vehicles. However, for large‐scale industrial applications, interfacial degradation between high‐voltage cathode active materials (CAMs) and solid‐state electrolytes (SSEs) needs to be overcome with a simple, cost‐effective solution. Surface coatings, which prevent the direct physical contact between CAM and SSE and in turn stabilize the interface, are considered as promising approach to solve this issue. In this work, an Al2 O3 /LiAlO2 coating for Li(Ni0.70 Co0.15 Mn0.15 )O2 (NCM) is tested for ASSBs. The coating is obtained from a recently developed dry coating process followed by post‐annealing at 600 °C. Structural characterization reveals that the heat treatment results in the formation of a dense Al2 O3 /LiAlO2 coating layer. Electrochemical evaluations confirm that the annealing‐induced structural changes are beneficial for ASSB. Cells containing Al2 O3 /LiAlO2 ‐coated NCM show a significant improvement of the rate capability and long‐term cycling performance compared to those assembled from Al2 O3 ‐coated and uncoated cathodes. Moreover, electrochemical impedance spectroscopy analysis shows a decreased cell impedance after cycling indicating a reduced interfacial degradation for the Al2 O3 /LiAlO2 ‐coated electrode. The results highlight a promising low‐cost and scalable CAM coating process, enabling large‐scale cathode coating for next‐generation ASSBs. Abstract : A low‐cost and simple dry‐processed Al2 O3 coating is used to improve the interfacial stability between solid‐state electrolyte and cathode active material in thiophosphate‐based all‐solid‐states batteries. A high‐temperature annealing affects various structural properties of the coating leading to a significant improvement of the electrochemical performance.